Precompetition warm-up in elite and subelite rhythmic gymnastics - Guidetti, L.; Di Cagno, A.; Gallotta, M. C.; Battaglia, C.; Piazza, M.; Baldari, C. (The Journal of Strength and Conditioning Research, 2009)
The aim of this study was to investigate which precompetition warm-up methodologies resulted in the best overall performance in rhythmic gymnastics. The coaches of national and international clubs (60 elite and 90 subelite) were interviewed. The relationship between sport performance and precompetition warm-up routines was examined. A total of 49% of the coaches interviewed spent more than 1 hour to prepare their athletes for the competition, including 45 minutes dedicated to warm-up exercises. In spite of previous studies' suggestions, the time between the end of warm-up and the beginning of competition was more than 5 minutes for 68% of those interviewed. A slow run was the activity of choice used to begin the warm-up (96%). Significant differences between elite and subelite gymnasts were found concerning the total duration of warm-up, duration of slow running, utilization of rhythmic steps and leaps during the warm-up, the use of dynamic flexibility exercises, competition performances repetition (p < 0.01), and utilization of imagery (p < 0.05). A precompetition warm-up in rhythmic gymnastics would include static stretching exercises at least 60 minutes prior to the competition starting time and the active stretching exercises alternated with analytic muscle strengthening aimed at increasing muscle temperature. Rhythmic gymnastics coaches at all levels can use this data as a review of precompetition warm-up practices and a possible source of new ideas.